2013
DOI: 10.1111/jocn.12036
|View full text |Cite
|
Sign up to set email alerts
|

Improving newborn pain management: systematic pain assessment and operators' compliance with potentially better practices

Abstract: Aims and objectivesThis quality improvement (QI) initiative was designed to develop systematic pain assessments and assess operators' compliance with potentially better practices identified by means of a structured PDCA (Plan-Do-Check-Act) process, in an effort to close the evidence-practice gap for pain management in the newborn. BackgroundPain control and prevention is imperative for ethical and clinical reasons and is pursued by the American Academy of Pediatrics as a standard requirement in the paediatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The precision of the statistical analysis was limited because the number of participating sites was small, but we confirmed a trend of increasing implementation rates of QI 1, 2, 3, 5, 6, 8, and 10. While other pain management quality improvement activities have been demonstrated in NICUs, 8 11 this report highlights possibilities for collaborative improvement in pain management across various types of organization of hospital management and various regions of hospitals in Japan. The key elements of this collaborative program, including (1) the presence of pain team leaders using PDSA cycles and leadership support for their activities from nurse managers and physician managers at each site, (2) a 2-day educational session with other participating sites, (3) a supportive communication structure involving experts and exchange of experiences among participating sites, and (4) availability of best practice information, might facilitate improvements in pain practice.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The precision of the statistical analysis was limited because the number of participating sites was small, but we confirmed a trend of increasing implementation rates of QI 1, 2, 3, 5, 6, 8, and 10. While other pain management quality improvement activities have been demonstrated in NICUs, 8 11 this report highlights possibilities for collaborative improvement in pain management across various types of organization of hospital management and various regions of hospitals in Japan. The key elements of this collaborative program, including (1) the presence of pain team leaders using PDSA cycles and leadership support for their activities from nurse managers and physician managers at each site, (2) a 2-day educational session with other participating sites, (3) a supportive communication structure involving experts and exchange of experiences among participating sites, and (4) availability of best practice information, might facilitate improvements in pain practice.…”
Section: Discussionmentioning
confidence: 90%
“…The use of QIs to monitor the progress of improvement efforts has been shown to be an effective method for improving the quality of practice. Previous quality studies have reported the use of QIs for pain assessment and pain relief by both local 8 , 9 and collaborative groups. 10 , 11 …”
Section: Background and Objectivementioning
confidence: 99%
“…In our study, we could not find such an improvement after questionnaires and even following educational sessions. Lago et al have noted that training staff in pain assessment, entering pain scores in medical records, and developing a pain protocol could increase the use of pain relief measures from 28% to 76% 23 . Spence et al 24 have shown that use of breastfeeding or sucrose analgesia has improved after an initiative which included audit and feedback, benchmarking, educational workshops on critical appraisal and audit of family awareness of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Following a preeducational and posteducational questionnaire and improving access to sucrose, they noticed increased utilisation of sucrose as non-pharmacological analgesia from 15% to 90%. Lago et al 2 have noted that training staff in pain assessment, entering pain scores in medical records and developing a pain protocol could increase the use of pain relief measures from 28% to 76%.…”
Section: Introductionmentioning
confidence: 99%